Mosaic partial tetrasomy 10: a rare prenatal diagnosis - Sarabando,Rita (2022)
Abstract Mosaic partial tetrasomy 10 is a rare chromosomal disorder. It has been associated with several fetal malformations and poor outcome. We report a case with prenatal diagnosis at 22 weeks of gestational age, whose second-trimester ultrasound scan showed several malformations. Fetal karyotype revealed a partial mosaic tetrasomy of chromosome 10 ([47,XY,+idic(10)(q11.2)[11]/46,XY[27]) classified as pathogenic. Medical termination of pregnancy was performed and fetal autopsy confirmed the ultrasound findings. There is only one case of tetrasomy 10p reported in the literature, with similar features and fetal malformations, and by sharing this rare case we hope to help in similar clinical scenarios.